Incidence of Seasonal Diarrhea among Children at Child’s Central Hospital - Abu- Ragheef, layla; Hussein, Abdul-Kadir (Iraqi National Journal of Nursing Specialties, 2007)
Objective: Diarrhea is a symptom of a variety of conditions may attack the child. It considered one of mam causes of mortality rates especially in low socio- economic level countries. The child can be easily got dehydration and pass from loss of too much body fluid and due to the Common thoueht of increasing the incidence of diarrhea during summer season, this study is done to find out the relation between the high incidences rate of diarrhea and weather variation Methodology: This survey conducted in AL- Markazi Child’s Teaching Hospital for the year 2005 the data were gathered from hospital records for the period (January - December) and age groups taxonomy used by hospital applied. Descriptive statistical analysis and diagrams used Results: The analysis revealed that the incidence of diarrhea happens all around the year and for the whole age groups. Summer results pointed out high ratio in relation to the results of spring winter and autumn seasons. Also more incidence seen among the age group (<2 months- one year) then the aee group (<5 years) held the second rank in getting diarrhea. Recommendations: The study recommended after analysis of data statistically, orientation about danger of diarrhea very necessary to whole society by different means especially the parents and issue firm legislation to keep the environment as much as it should be free from outbreak of diarrhea.